Changes In the Composition of Unsaturated Fatty Acids in The Blood Plasma In Men Living in Rural Areas of the Novosibirsk Region, Depending on Alcohol Consumption - V. S. Shramko; E. M. Stakhneva; E. V. Kashtanova; L. V. Shcherbakova; Ya. V. Polonskaya; Yu. I. Ragino (Архивъ внутренней медицины, 2025)
The aim of the study was to investigate differences in the content of unsaturated fatty acids (UFA) in blood plasma in men living of rural areas of the Novosibirsk region, depending on their alcohol status. Materials and methods: as part of a single-stage epidemiological study in the Novosibirsk region, rural residents (men) aged 60.04±10.55 (from 35 to 74 years) were examined. The alcohol status of the participants was determined by means of a questionnaire. The number of different alcoholic beverages was recalculated in doses of pure alcohol. All study participants were divided into three groups based on alcohol consumption per week: group 1 — low alcohol consumption (LC); group 2 — moderate alcohol consumption (MC); group 3 — high alcohol consumption (HC). The levels of omega-3, -6, and -9 UFA in blood plasma were determined by high-performance liquid chromatography. Results: It was found that the group of men with HC had higher concentrations of omega-3 alpha-linolenic acid (p=0,041) and omega-6 digomo-gamma-linolenic (p=0,002), docosatetraenoic (p=0,017), docosapentaenoic (p=0,023) UFA in blood, compared with group of men with LC. Conclusions: In the study, we found statistically significant differences in blood concentrations of alpha-linolenic acid, digomo-gammalinolenic acid, docosathetraenoic acid, and docosapentaenoic acid unsaturated fatty acids were obtained in men aged 35-74 years living in rural areas of the Novosibirsk region, depending on alcohol consumption.